2020
DOI: 10.1039/d0nr05255h
|View full text |Cite
|
Sign up to set email alerts
|

Double resonant plasmonic lattices for Raman studies

Abstract: We demonstrate radiation induced enhancement of both the incoupling of Raman excitation wavelength as well as Raman signal in plasmonic nanoparticle lattices. Rectangular nanoparticle lattices show two independently controllable lattice...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…4. We observe three clear Raman peaks 58 related to R6G molecules, namely at 1290 cm −1 , 1345 cm −1 , and 1490 cm −1 , and one less pronounced peak at 1650 cm −1 . Single triangles appear to exhibit only a weak R6G Raman signal with two distinguishable peaks at 1345 cm −1 and 1490 cm −1 (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…4. We observe three clear Raman peaks 58 related to R6G molecules, namely at 1290 cm −1 , 1345 cm −1 , and 1490 cm −1 , and one less pronounced peak at 1650 cm −1 . Single triangles appear to exhibit only a weak R6G Raman signal with two distinguishable peaks at 1345 cm −1 and 1490 cm −1 (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…1c) and the procedures are explained in detail elsewhere. 58 A commercial Renishaw InVia Reflex Raman microscope was used to measure Raman signals of R6G on both samples using a laser excitation wavelength of 785 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Choosing a different lattice (rectangular, hexagonal) for the dielectric cavities arrangement would offer even more degrees of freedom and strongly influence polarization. It has been recently shown that an array of subwavelength metallic structures can provide strong Raman enhancement at specifically tuned wavelengths by adapting the lattice constant of the structure in two orthogonal directions [33]. Operating on the same principle as our concept of two-dimensionally patterned dielectric multilayer, we open a path to similar benefits with the additional advantage of a wider choice of materials for a broader range of applications with compatibility in the bio-medical domain.…”
Section: Resultsmentioning
confidence: 88%
“…From these three spectra we can distinguish very clear peaks at 1290, 1345, and 1490 cm −1 (corresponding to the wavelengths of 873, 877, and 890 nm at the 785 nm excitation), which are associated with the prominent R6G Raman transitions. 50 Due to practical reasons, we base our analysis here on normalized spectra, as the most relevant quantity, namely the signal-to-background ratio becomes most evident using this method. First, the BBS sample exhibits only very moderate Raman enhancements (light blue).…”
Section: Resultsmentioning
confidence: 99%